Role of Municipal Council in Increasing Citizen Participation at the Local Budget Process - Memet Memeti; Veli Kreci (Central European Public Administration Review)
The paper explores the role of the municipal councilors in the budget process in the Republic of Macedonia as well as their role in motivating citizen participation in the budgetary process in the Republic of Macedonia. We demonstrate that municipalities in the Republic of Macedonia employ various forms of participatory mechanisms in the process of public policies and budgets according to their context. There are vivid dissimilarities in terms of opportunities and scope of citizen participation as well as discrepancies of councilors capacity to facilitate this process when cross-matching information and data derived from small rural and bigger urban municipalities. It is evident that very little has been accomplished in terms of defining uniformed processes and developing systems related to the relations between councilors and local community. We identify barriers that are impediment to a genuine involvement of the councilors as mediators between the Mayor and the community in the local budgeting process. We argue that any policy intervention in this dimension ought to be tailor-made, hence every municipality has its specific features that ought to be taken into account when designing an intervention to address shortcomings of the processes and the systems.